2003
DOI: 10.1161/01.cir.0000065221.06430.ed
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Assessment of Reperfusion in Acute Myocardial Infarction by Myocardial Blush Grade

Abstract: Background-Angiographic successful reperfusion in acute myocardial infarction has been defined as TIMI 3 flow.However, TIMI 3 flow does not always result in effective myocardial reperfusion. Myocardial blush grade (MBG) is an angiographic measure of myocardial perfusion. We hypothesized that optimal angiographic reperfusion is defined by TIMI 3 flow and MBG 2 or 3. Methods and Results-In 924 consecutive patients with TIMI 3 flow after angioplasty for acute myocardial infarction, we prospectively studied the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
125
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(134 citation statements)
references
References 48 publications
8
125
0
1
Order By: Relevance
“…The frequency of MO of just over 30% observed in our population study with NSTEMI is close to that observed in patients with STEMI determined by CMR, myocardial contrast echography and angiographic methods (TIMI frame count score, myocardial blush grade) [1,2,3,4,5,6,7, 17, 18,20,21,22]. …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The frequency of MO of just over 30% observed in our population study with NSTEMI is close to that observed in patients with STEMI determined by CMR, myocardial contrast echography and angiographic methods (TIMI frame count score, myocardial blush grade) [1,2,3,4,5,6,7, 17, 18,20,21,22]. …”
Section: Discussionsupporting
confidence: 84%
“…Experimentally induced MO was initially described only after transient but complete obstruction (TIMI = 0) of a coronary artery [26]. In clinical studies, the infarct-related artery status at baseline correlated well (p < 0.05) with the microvascular status, and patients with MO had a significantly lower TIMI score at baseline than patients without [1, 20, 27]. One of the reasons for this difference is the low number of patients in our study, and therefore, the low statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, effective epicardial and microcirculatory reperfusion, which was more frequently observed in patients treated with the MGuard than with a standard metallic stent, may improve long-term survival. 3,4,14 These observations require confirmation in larger randomized trials.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism of NR in primary angioplasty is thought to include peripheral embolism caused by debris (that originates in and is flushed from the atherosclerotic plaque), ischemia/reperfusion injury, coronary anatomy variability and individual predisposition [2]. NR predictors include male gender, advanced age [3], multivessel coronary disease [4], impaired kidney function [5], an elevated thromboxane A 2 (TXA 2 ) level [6], increased platelet reactivity [7], high levels of C-reactive protein (CRP) [8] and endothelin-1 [9], neutrophilia [10], elevated baseline glucose [3], anterior wall myocardial infarction [3] and a visible free-floating thrombus in a target coronary vessel [11]. …”
Section: Introductionmentioning
confidence: 99%